Analysis of potential application of biogas fuel in modern compression-ignition engines - Śmieja, Michał; Wierzbicki, Sławomir (International Conference “Environmental Engineering”, 2017)
Limited fossil fuel supplies and the necessary reduction in toxic fumes emission to the atmosphere are the main motives in conducting a search for the new, effective energy supplies. The one with potential is biogas. It is the product of natural fermentation processes of municipal waste in landfills or is produced in biogas plants out of agricultural and green waste. Due to creation under different conditions, its chemical composition varies. This is enormous obstacle in its effective application. Biogas is easily applied to fuel spark-ignition engines however intensive attempts are made to employ it in much more effective compression-ignition engines. Application of biogas require the use of dua-luel CI engine. The point of the research described in this paper is to show the influence of different methane carbon dioxide composition ratio in biogas on dual-uel CI engine effectiveness.